Yield and phenological indices of wheat as affected by exogenous fertilization of Zinc and Iron - Jalal, Arshad [UNESP]; Shah, Shahen; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP]; Khan, Ayesha; Shah, Tariq; Hussain, Zawar; Younis, Muhammad; Ilyas, Muhammad (Univ Federal Rural Pernambuco, 2020)
Micronutrients (zinc and iron) play a vital role in the functioning of all living organisms. These nutrients are indispensable for plant nourishment and development - though required in small amount. The current research work was performed at the Agronomy Research Farm, The University of Agriculture Peshawar in winter, 2015-16. Combinations of soil applied Zn levels (5, 10, 15 and 20 kg ha(-1)) and Fe levels (5, 10, 15 and 20 kg ha(-1)) with a control were allotted randomly to the experimental units using randomized complete block design. The results elucidated that days to anthesis, plant height, productive tillers, yield and yield components of wheat were significantly inclined with Zn and Fe levels. The plots enriched with 15 kg Zn ha(-1) and 10 kg Fe ha(-1) exhibited higher grain yields (3775 and 3802 kg ha(-1), respectively). Results conceded that the interaction for Zn and Fe was significant for days to anthesis. It was concluded that the plots fertilized with 15 kg Zn ha(-1) and 10 kg Fe ha(-1) resulted in improved yield and yield components. Hence, fertilization of plots with 15 kg Zn ha(-1) and 10 kg Fe ha(-1) is recommended for improved wheat yield in the agro-climatic condition of Peshawar.
Keywords: grain yield; growth; micronutrients; Triticum aestivum